A Human STAT1 Gain-of-Function Mutation Impairs CD8(+) T Cell Responses against Gammaherpesvirus 68 - Qian, Wei (J Virol, 2019)
Autosomal dominant STAT1 mutations in humans have been associated with chronic mucocutaneous candidiasis (CMC), as well as with increased susceptibility to herpesvirus infections. Prior studies have focused on mucosal and Th17-mediated immunity against Candida, but mechanisms of impaired antiviral immunity have not previously been examined. To begin to explore the mechanisms of STAT1-associated immunodeficiency against herpesviruses, we generated heterozygous STAT1 R274W knock-in mice that have a frequently reported STAT1 mutation associated in humans with susceptibility to herpesvirus infections. In primary macrophages and fibroblasts, we found that STAT1 R274W had no appreciable effect on cell-intrinsic immunity against herpes simplex virus 1 (HSV-1) or gammaherpesvirus 68 (γHV68) infection. However, intraperitoneal inoculation of mice with γHV68 was associated with impaired control of infection at day 14 in STAT1 R274W mice compared with that in wild-type (WT) littermate control animals. Infection of STAT1 R274W mice was associated with paradoxically decreased expression of IFN-stimulated genes (ISGs) and gamma interferon (IFN-γ), likely secondary to defective CD4(+) and CD8(+) T cell responses, including diminished numbers of antigen-specific CD8(+) T cells. Viral pathogenesis studies in WT and STAT1 R274W mixed bone marrow chimeric mice revealed that the presence of WT leukocytes was sufficient to limit infection and that antigen-specific STAT1 R274W CD8(+) T cell responses were impaired even in the presence of WT leukocytes. Thus, in addition to regulating Th17 responses against Candida, a STAT1 gain-of-function mutant impedes antigen-specific T cell responses against a common gammaherpesvirus in mice. IMPORTANCE Mechanisms of immunodeficiency related to STAT1 gain of function have not been previously studied in an animal model of viral pathogenesis. Using virological and immunological techniques, we examined the immune response to γHV68 in heterozygous mice that have an autosomal dominant mutation in the STAT1 coiled-coil domain (STAT1 R274W). We observed impaired control of infection, which was associated with diminished production of gamma interferon (IFN-γ), fewer effector CD4(+) and CD8(+) T cells, and a reduction in the number of antigen-specific CD8(+) T cells. These findings indicate that a STAT1 gain-of-function mutation limits production of antiviral T cells, likely contributing to immunodeficiency against herpesviruses.